2018
DOI: 10.1097/gme.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Association between waist-to-height ratio and anxiety in middle-aged women: a secondary analysis of a cross-sectional multicenter Latin American study

Abstract: In this series, WHtR was associated with anxiety in middle-aged women. It is advisable to further study this anthropometric measure in order for it to be incorporated in the routine clinical practice and evaluation of middle-aged women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…In contrast to our results, a recent study from the Netherlands Mental Health Survey and Incidence Study-2 found obesity, based on BMI, to be a significant risk factor for the onset of anxiety disorders during a three-year follow-up period [53]. Other studies have also observed a significant association between WHR and WHtR and depression and anxiety, particularly among women [56,57].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, a recent study from the Netherlands Mental Health Survey and Incidence Study-2 found obesity, based on BMI, to be a significant risk factor for the onset of anxiety disorders during a three-year follow-up period [53]. Other studies have also observed a significant association between WHR and WHtR and depression and anxiety, particularly among women [56,57].…”
Section: Discussioncontrasting
confidence: 99%
“…There is disagreement over the link between obesity and mental health disorders as some studies show significant effects [53][54][55][56][57] while others do not [56,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…This study shows a positive and significant correlation between Hamilton's Depression rating scale and BMI in agreement with 28 showed a strong association between mental disorder and being obese or overweight amongst females compared to males. 29…”
Section: Discussionmentioning
confidence: 99%
“…So that, different studies indicated that obesity may has positive correlation with depression and anxiety (7) (8) (9). For example, Karen J et al in a recent publication found that waist-to-height ratio is associated with anxiety in Latin American middle-aged women (10), whereas depression was associated with body mass index (BMI) in American women in midlife (11), (12), (13).…”
Section: Introductionmentioning
confidence: 99%